Analysis of Lumped Network Equivalent Circuit Model for Meander Line Antenna - M.Pandimadevi; R. Tamilselvi; M. Parisa Beham (The Bioscan, 2025)
Meander Line antennas have gained popularity in recent years when miniaturization is needed in radio frequency circuits. The widespread use of this antenna has led to the lack of simple analytical models, except for those that utilize sophisticated numerical methods. This paper proposes a circuit design for a meander line patch antenna that utilizes the lumped network phenomenon. The circuit model being proposed has twenty sections, which incorporate T-networks of inductor and capacitors. A dual band frequency of 2.1 GHz and 3.2 GHz was obtained through circuit theory analysis, which was modelled and solved. The circuit modelling is also done using LTspice software. It is observed that S11 parameter obtained from the circuit modelled in LTspice is also approximately resonant at dual frequencies computed from the circuit analysis thereby validating the proposed approach.